2014
DOI: 10.1186/1471-2407-14-545
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis inhibitor-5 overexpression is associated with tumor progression and poor prognosis in patients with cervical cancer

Abstract: BackgroundThe apoptosis inhibitor-5 (API5), anti-apoptosis protein, is considered a key molecule in the tumor progression and malignant phenotype of tumor cells. Here, we investigated API5 expression in cervical cancer, its clinical significance, and its relationship with phosphorylated extracellular signal-regulated kinase 1 and 2 (pERK1/2) in development and progression of cervical cancer.MethodsAPI5 effects on cell growth were assessed in cervical cancer cell lines. API5 and pERK1/2 immunohistochemical stai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
44
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 34 publications
4
44
0
1
Order By: Relevance
“…We confirmed the presence of API5 in active caspase-2-containing complexes by immunoblots ( Fig 1B). As shown before [14,19], API5 antibodies detect a double band in HeLa cells recognizing both the 55-and 57-kDa isoforms ( Fig 1B). Gel filtration analysis revealed that API5 and caspase-2 are shifting towards high molecular weight fractions in PFT-treated cells ( Fig 1C).…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…We confirmed the presence of API5 in active caspase-2-containing complexes by immunoblots ( Fig 1B). As shown before [14,19], API5 antibodies detect a double band in HeLa cells recognizing both the 55-and 57-kDa isoforms ( Fig 1B). Gel filtration analysis revealed that API5 and caspase-2 are shifting towards high molecular weight fractions in PFT-treated cells ( Fig 1C).…”
Section: Resultssupporting
confidence: 81%
“…API5 also inhibits E2F1‐dependent apoptosis in a transcription‐independent manner . Recent studies revealed that API5 is highly expressed in various cancers and associated with poor prognosis especially in NSCLCs and cervical cancer; however, the molecular mechanisms behind API5‐mediated cell survival remains poorly understood . Here, we reveal that API5 directly binds to the CARD domain of caspase‐2 and prevents its dimerization and activation.…”
Section: Introductionmentioning
confidence: 80%
“…The API5 protein suppresses apoptosis induced by the transcription factor E2F1, and interacts with and negatively regulates Acinus, a nuclear factor involved in apoptotic DNA fragmentation. The API5 gene is involved in many human diseases including diabetes and cancers (Cho et al, 2014; Noh et al, 2014; Peng et al, 2015; Ramdas et al, 2011). However, API5 has not been reported to be involved in skeletal muscle development.…”
Section: Discussionmentioning
confidence: 99%
“…SCYL1BP1 encodes SCY1-like 1-binding protein 1, a regulator of the p53 pathway with tumour-suppressive function [30][31][32]. API5 encodes the protein apoptosis inhibitor 5, which is reported to be a suppressor of apoptosis and to play a key role in tumour progression [33,34]. However, the relationships of these SNPs and other genes are largely unknown.…”
Section: Discussionmentioning
confidence: 99%